Implementation of HOTS-Based Evaluation in Learning Introductory Christian Religious Education For First Semester PAK Study Program Students Academic Year 2024/2025 at IAKN Tarutung - Simatupang, Ronny; Sihombing, Lince; Simatupang, Hasudungan (LPPM IAKN Tarutung, 2025)
Learning evaluation should be able to provide useful feedback for learning improvement, as well as provide a clear picture of the achievement of educational goals. The Introduction to Christian Religious Education course should be a forum that educates students to deeply understand Christian teachings. Students are not only required to understand religious teachings theoretically, but also to be able to analyze, evaluate, and relate these teachings to real life. This study aims to analyze the Implementation of HOTS (Higher Order Thinking Skills) Based Evaluation in Learning Introduction to Christian Religious Education Students of PAK Study Program Semester One Year Academic 2024/2025 at IAKN Tarutung. The method used is qualitative research method type of field research. The data collection techniques used in this research are observation, interview, and documentation. This research uses descriptive analysis techniques to describe the results of the data obtained. Data analysis includes data collection, data reduction, data presentation, and data verification. The validity of the data obtained in this study was checked using triangulation techniques. The results of the study indicate that the Implementation of HOTS Based Evaluation in Learning Introduction to Christian Religious Education First Semester PAK Study Program Students Year Academic 2024/2025 at IAKN Tarutung has been carried out by the lecturer teaching the course. The HOTS Based Evaluation Implementation Process in Introductory Christian Religious Education Learning that has been carried out is: 1) HOTS (Higher Order Thinking Skills) based evaluation planning in Introduction to Christian Religious Education learning which includes: Determining evaluation objectives, compiling question grids and compiling questions; 2) Implementation of HOTS based evaluation in learning Introduction to Christian Religious Education which includes: collecting data, verifying data, processing and analyzing data, interpreting and drawing conclusions; 3) Follow-up evaluation based on HOTS in learning Introduction to Christian Religious Education.